The Automated External Defibrillator: Heterogeneity of Legislation, Mapping and Use across Europe. New Insights from the ENSURE Study - Enrico Baldi (MDPI AG, 2021)
Introduction: The rapid use of an automated external defibrillator (AED) is crucial for increased survival after an out-of-hospital cardiac arrest (OHCA). Many factors could play a role in limiting the chance of an AED use. We aimed to verify the situation regarding AED legislation, the AED mapping system and first responders (FRs) equipped with an AED across European countries. Methods: We performed a survey across Europe entitled “European Study about AED Use by Lay Rescuers” (ENSURE), asking the national coordinators of the European Registry of Cardiac Arrest (EuReCa) program to complete it. Results: Nineteen European countries replied to the survey request for a population covering 128,297,955 inhabitants. The results revealed that every citizen can use an AED in 15 countries whereas a training certificate was required in three countries. In one country, only EMS personnel were allowed to use an AED. An AED mapping system and FRs equipped with an AED were available in only 11 countries. The AED use rate was 12–59% where AED mapping and FR systems were implemented, which was considerably higher than in other countries (0–7.9%), reflecting the difference in OHCA survival. Conclusions: Our survey highlighted a heterogeneity in AED legislation, AED mapping systems and AED use in Europe, which was reflected in different AED use and survival.